2017
DOI: 10.1186/s12983-017-0215-z
|View full text |Cite
|
Sign up to set email alerts
|

Vertical leaping mechanics of the Lesser Egyptian Jerboa reveal specialization for maneuverability rather than elastic energy storage

Abstract: BackgroundNumerous historical descriptions of the Lesser Egyptian jerboa, Jaculus jaculus, a small bipedal mammal with elongate hindlimbs, make special note of their extraordinary leaping ability. We observed jerboa locomotion in a laboratory setting and performed inverse dynamics analysis to understand how this small rodent generates such impressive leaps. We combined kinematic data from video, kinetic data from a force platform, and morphometric data from dissections to calculate the relative contributions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 44 publications
6
32
0
Order By: Relevance
“…In a recent study of desert kangaroo rats, we showed that while the majority of mechanical work for vertical jumping is delivered at the ankle, approximately 40% of this energy is transferred from proximal muscles (Schwaner et al, 2017), and in a previous study we showed that proximal to distal energy transfer also likely plays an important role in horizontal accelerations by tammar wallabies (McGowan et al, 2005b). The ratio of the moment arms of the ankle extensors at the ankle and knee is approximately 2:1 and is remarkably similar in macropods and bipedal rodents (Alexander and Vernon, 1975;Moore et al, 2017b;Rankin et al, 2018). If the ankle extensor muscle-tendon unit were to act exclusively as a strut, a 4-bar linkage would be created and any torque generated at the knee would be doubled at the ankle.…”
Section: Hypothesis 1: Bipedal Hopping Evolved To Enhance Locomotor Esupporting
confidence: 55%
See 3 more Smart Citations
“…In a recent study of desert kangaroo rats, we showed that while the majority of mechanical work for vertical jumping is delivered at the ankle, approximately 40% of this energy is transferred from proximal muscles (Schwaner et al, 2017), and in a previous study we showed that proximal to distal energy transfer also likely plays an important role in horizontal accelerations by tammar wallabies (McGowan et al, 2005b). The ratio of the moment arms of the ankle extensors at the ankle and knee is approximately 2:1 and is remarkably similar in macropods and bipedal rodents (Alexander and Vernon, 1975;Moore et al, 2017b;Rankin et al, 2018). If the ankle extensor muscle-tendon unit were to act exclusively as a strut, a 4-bar linkage would be created and any torque generated at the knee would be doubled at the ankle.…”
Section: Hypothesis 1: Bipedal Hopping Evolved To Enhance Locomotor Esupporting
confidence: 55%
“…A rapid vertical or lateral leap, followed by aerial reorientation, to evade the ballistic strike of a predator is likely under strong selective pressure in many small bipedal hoppers. The morphological adaptions of the hindlimbs are well suited for generating the rapid accelerations and high mechanical power output needed to produce the extreme jumping performance seen in many species, with jumps often reaching as high as 10 times the animal's hip height (Bartholomew and Caswell, 1951;Moore et al, 2017b;Schwaner et al, 2017). The elongated hindlimbs of bipedal hoppers enable them to accelerate the body over longer periods of time (Alexander, 1995), and hoppers tend to have substantially more hindlimb muscle mass relative to similarly sized quadrupeds (Berman, 1980;Grand, 1990).…”
Section: Hypothesis 1: Bipedal Hopping Evolved To Enhance Locomotor Ementioning
confidence: 99%
See 2 more Smart Citations
“…Muscle is not required for autopod tendon formation or maintenance in mice, but the tendons that develop in a muscleless or a paralyzed mouse are thinner and less well organized (Huang et al, 2015). It is 405 therefore possible that muscle is initially required in the fetus and neonate for tendons to establish sufficient architecture from origin to insertion so that the tendon, after further growth, can withstand high locomotor forces in the adult (Lochner et al, 1980;Moore et al, 2017).…”
Section: Discussionmentioning
confidence: 99%